Media Belajar Berbasis QR-code untuk Memperkenalkan Arsitektur Nusantara di SD Negeri Gairipim Mappi - Papua - Roosandriantini, Josephine; Wahyuningsih, Yulia; Christela Oktaviani, Yohana; Amstrong Hayong, Emanuel (Jurnal Pengabdian Masyarakat Charitas, 2024)
In this digital era, almost every aspect of human life relies on technology, including education, business, government, and daily life. One example of technology widely used in various fields is QR-code technology. Unfortunately, this comfort cannot be felt in other regions of Indonesia. The lack of information impacts the slow learning development in areas commonly referred to as 3T regions, (Tertinggal, Terdepan, Terluar). Therefore, it is necessary to address this condition. Children in the 3T region have the right to equality in learning and accessing knowledge. Thus, the author takes the initiative to develop learning media that trains the fine motor skills of elementary school students in Gairipim, Papua, by their age. The method used in this community service activity is a qualitative descriptive method. The provision of engaging and interactive learning media is expected to spark curiosity and a desire to continue learning. This activity considers the limited internet access in remote areas, so the applications installed on the devices do not require internet connectivity. Therefore, users can achieve their goals even with minimal internet access. In this way, students at SD Negeri Gairipim can gain equal access to learning and enjoy modern learning media.